Simultaneous, Bilateral Ophthalmoplegia as the Presenting Sign of Paediatric Multiple Sclerosis: Case Report and Discussion of the Differential Diagnosis. (August 2014) - Adam, Murtaza K.; Krespan, Kelly; Moster, Mark L.; Sergott, Robert C.
Abstract An 11-year-old female developed bilateral oculomotor nerve palsies without pupillary involvement and bilateral optic neuropathy as the presenting signs of paediatric multiple sclerosis (MS). Although ocular mono-neuropathies have been reported, this is the first bilateral mono-neuropathy reported in a paediatric patient due to MS. The differential diagnosis and evaluation for bilateral ophthalmoplegia are discussed in detail.